Optimizing Employee Performance at Kiki Tailor Leather & Textile to Enhance Sales Revenue - Setiawan, Kevin Pradista; Agung Gde Alit Wiradyatmika, Anak (Jurnal Karya Abdi Masyarakat, 2023)
Kiki Tailor Leather & Textile operates as a retail business through its official store located in Nusa Dua, Bali, with a strong emphasis on optimizing employee performance to enhance sales revenue. The success of the company is largely dependent on the performance of its employees, making it crucial for businesses to continuously improve employee productivity to meet organizational goals. One of the most effective strategies for achieving this is through a connection between employee compensation, motivation, and job satisfaction. By focusing on these factors, businesses can foster a more engaged and productive workforce, which in turn can drive sales growth. In this context, Kiki Tailor Leather & Textile could benefit from enhancing its digital marketing efforts. Recruiting specialized personnel in digital marketing could help increase the company’s visibility and reach, contributing to long-term improvements in sales performance. This approach not only aims to optimize internal processes but also responds to external market demands, ensuring the company remains competitive. As the business environment continues to evolve, integrating modern marketing strategies with optimized employee performance will be essential for sustaining growth and profitability in the retail sector.